STUDI PENGGUNAAN UV-VIS SPECTROSCOPY DAN KEMOMETRIKA UNTUK MENGIDENTIFIKASI PEMALSUAN KOPI ARABIKA DAN ROBUSTA SECARA CEPAT - Meinilwita Yulia; Riri Iriani; Diding Suhandy; Sri Waluyo; Cicih Sugianti (The University of Lampung, 2017)
There are two popular coffees in Indonesia, namely Arabica and Robusta coffees. Arabica coffee has a better quality than Robusta do. This research aimed to identify the purity of Arabica coffee; and Robusta as mixture ingredient, by using technology of UV-Vis spectroscopy and multivariate analysis, with a method of soft independent modelling of class analogy (SIMCA) and principal component analysis (PCA). The research was conducted using coffee powder with size 0,297 millimeters (50 mesh).The research used 100 samples; sample 1-50 (1 g of Arabica), sample 51-60 (0,8 g of Arabica and 0,2 of Robusta), sample 61-70 (0,7 g of Arabica and 0,3 g of Robusta), sample 71-80 (0,6 g of Arabica and 0,4 of Robusta) sample 81-90 (0,5 g of Arabica and 0,5 g of Robusta), sample 91-100 (0,4 g of Arabica and 0,6 g of Robusta). The result of classification showed that method of PCA and SIMCA are able to classify the mixture of pure Arabica. PC1 explained 77% various datas, and PC2 explained 10% various datas, whilst from data classification SIMCA obtained the precentage score onaccuracy 56%, sensitivitas 58%, and spesifisitas 0%.Keywords: Arabica coffee, Robusta coffee, PCA, SIMCA, UV-Vis spectroscopy